Implementation of Human Resource Management in Improving Employee Performance of PT. Ranugas Berkah Persada Samarinda - Mahardika, Swadia Gandhi; Wahyuni, Sri (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
This study analyzes the implementation of Islamic value-based human resource management (HRM) at PT. Ranugas Berkah Persada Samarinda and its impact on employee performance. Islamic values, such as Siddiq (honesty), Amanah (trustworthiness), Fathonah (intelligence), and Tabligh (good communication), are applied in the recruitment process, training, and performance evaluation. This study uses a qualitative approach with a case study method. Primary data were obtained through in-depth interviews with directors and employees, as well as direct observation, while secondary data in the form of internal company documents were analyzed to strengthen the research results. The results showed an increase in operational productivity by 15%, job satisfaction reached 85%, and a decrease in turnover rate to 5%. These findings confirm that Islamic value-based HRM contributes to creating a productive, harmonious, and sustainable work environment. This study also provides strategic recommendations for similar companies to adopt Islamic values as the basis for human resource management.